On a geometric study of a class of normalized functions defined by Bernoulli’s formula - Rabha W. Ibrahim; Ibtisam Aldawish; Dumitru Baleanu (Advances in Difference Equations, 2021)
Abstract The central purpose of this effort is to investigate analytic and geometric properties of a class of normalized analytic functions in the open unit disk involving Bernoulli’s formula. As a consequence, some solutions are indicated by the well-known hypergeometric function. The class of starlike functions is investigated containing the suggested class.